2020
DOI: 10.3390/ijms21239150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Selective RelA Inhibitor Based on DSE-FRET Screening Methods

Abstract: Nuclear factor-κB (NF-κB) is an important transcription factor involved in various biological functions, including tumorigenesis. Hence, NF-κB has attracted attention as a target factor for cancer treatment, leading to the development of several inhibitors. However, existing NF-κB inhibitors do not discriminate between its subunits, namely, RelA, RelB, cRel, p50, and p52. Conventional methods used to evaluate interactions between transcription factors and DNA, such as electrophoretic mobility shift assay and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Nevertheless, the literature reports such data for compounds from different chemical classes. Shiroma et al (2020) [77], after a virtual screening, identified compound A55 (2-(3-carbamoyl-6-hydroxy-4-methyl-2oxopyridin-1(2H)-yl)acetic acid) as a selective inhibitor of RelA(p65)-DNA binding. The molecular docking result showed that this compound interacted with the Tyr36 residue of NF-κB, which is also involved in the interaction between EZ and this protein target.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the literature reports such data for compounds from different chemical classes. Shiroma et al (2020) [77], after a virtual screening, identified compound A55 (2-(3-carbamoyl-6-hydroxy-4-methyl-2oxopyridin-1(2H)-yl)acetic acid) as a selective inhibitor of RelA(p65)-DNA binding. The molecular docking result showed that this compound interacted with the Tyr36 residue of NF-κB, which is also involved in the interaction between EZ and this protein target.…”
Section: Discussionmentioning
confidence: 99%